KETERSEDIAAN SARANA AKSESIBILITAS PENYANDANG DISABILITAS di PUSAT LAYANAN PUBLIK PEMERINTAH KOTA MANADO - Palar, Novie R. A; Londa, Very Y; Goni, Shirley Y. V. I. Goni Y. V. I.; Kandowangko, Nicolaas (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2023)
Persons with Disabilities have the right to access public facilities. However, until now there are still very few facilities that can support their activities in public service centers such as government offices. The right to accessibility is part of human rights and is regulated based on state policy. This study aims to analyze the availability of facilities or facilities related to disability accessibility in Manado city government public service centers. The research design used is a qualitative case study approach. Data was collected through direct interviews and interviews using new technological tools (zoom) adapted to the situation of the informants, as well as observations at Manado City Government public service centers to identify the availability of facilities. Data analysis used an interactive analysis model with the stages of data reduction, data display and conclusion drawing/verification. The research findings are that the accessibility of persons with disabilities at the Manado City Government Service Center in terms of the availability of facilities is not in accordance with the policy mandate. The facilities available to support the delivery of services in the fields of population administration, health and education in the City of Manado are general in nature and intended for all people. Not specifically available for persons with disabilities or people with special needs. The main cause of this is due to non-compliance in implementing policies. Another contributing factor is that the government has not made people with special needs a priority in service.